Saber da não violência na formação docente: processos autocompositvos como mediação às violências no contexto escolar - Ferrão, Iara da Silva (2020)
Violence is a phenomenon that must be understood based on conditions of the most diverse orders, including cultural, economic, political and psychosocial ones. School-based violence is an emerging theme in contemporary times, given the data on high levels of violence in / for school. The main objective of this work is to investigate the knowledge of non-violence in teacher education and the self-composing processes as mediations for school violence. Thus, it aims to understand the importance of teacher training and the knowledge of the profession and to present the “knowledge of non-violence” as a possibility to work with the ongoing violence at school. In addition, it aims to reflect on the performance of the educator's formative and normative role, which operates in a context permeated by multiple violence and, finally, to investigate how the theme of self-composition to transform crises, conflicts and / or violence (Mediation and Restorative Justice) / JR) can be a point of reference for contemporary educational actions, more specifically in teacher education. The route presents in its broad spectrum the hermeneutic understanding of the themes of violence in schools, as well as the profession of teacher training, self-composition of conflicts and non-violence. It unfolds in the interface of the Philosophy of Education and in the contributions to the research line LP1 (Teaching, Knowledge and Professional Development). The methodological path used was Hermeneutics, by Hans-Georg Gadamer, understanding that the textual analysis procedure, hermeneutically oriented, seeks to understand the meaning of the theme, as well as, to confront it with its original context, establishing points of contact and reconstruction . Hermeneutics aims to give context to the text and thus produce the mediation of meaning in a comprehensive horizon resulting from the fusion of the reader's understanding with the author of the work, in their respective historical times. Starting from the understanding that researching is walking; to understand, to construct meaning, the guiding question that arises to think is: to what extent, the knowledge of non-violence in teacher training and self-composing processes can be considered mediations to school violence? In this work, theoretical forces were gathered to defend the thesis that violence is the exact opposite of education and, in this sense, the need to put into circulation throughout this construct the idea of knowledge of non-violence, as a way of making a “ training ”of teachers against barbarism. The knowledge of non-violence is situated as a philosophical refusal to the ongoing violence and as a way to build a culture of peace at school. Thus, it aims to reframe concepts about JR, Conflict Mediation and JR Circles that share, in a maieutic way, the authors' experiences. Finally, betting on the locus of teacher training and the maxim that interrogates “so what to educate”, affirming a reflexive posture of a philosophical nature crossed by the dimension of the formative experience that mobilizes deeper knowledge, based on art, culture and classics. It recognizes that there is still a lot to be done in relation to the themes presented, but that this work proposes to make its contribution in the school and teacher training spaces.